Averaging of evolution equations disturbed by random processes with jumps - Kolomiets , Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Weak convergence of measures generated by solutions of an evolutionary equation dependent on a small parameter to the unique solution of the martingale problem corresponding to the stochastic evolutionary equation is proved. The coefficients of the initial equation depend on random Markov processes with jumps.